Auditoría de gestión a los inventarios y su incidencia en la rentabilidad de la empresa ferreteria “JM Ajila”, canton Quevedo, periodo 2012 - Moreira Pinargote, Wilmer Stalin (2015)
This research was conducted at the hardware store "JM Ajila" located on the street October 7 between 7th and 8th. Facing Bay Mall, in order to run an audit of management inventories and their impact on the profitability of the hardware "JM ajila" period 2012, for which different methods which were inductive, deductive and analytical methods used for completion of the audit report. It began with the application of techniques such as observation, interviews, and notes; Information was collected on the area involved, and made a brief but necessary overall investigation of the warehouse area. With the knowledge gained was reached defining the problem which is identified as the audit to inventories affects profitability. With the identification of the problem was necessary to consult the theory through a comprehensive review, to have knowledge regarding the valuation methods and valuation of inventories identified. Depending on the results of the evaluation of internal control with a confidence level of 82% (upper-middle), and a risk level of 18%, obtaining sufficient, competent, and relevant evidence to support the findings. In the final stage it disclosed the comments, conclusions and recommendations aimed at improving the methods used to carry out inventories and inventory control.